2017
DOI: 10.1007/s00340-017-6790-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically deposited tungsten disulfide saturable absorber for low-threshold Q-switched erbium-doped fiber laser

Abstract: In this paper, we report a Q-switched erbium-doped fiber laser incorporating tungsten disulfide (WS 2 ) as the saturable absorber. A direct mechanical deposition technique using a scotch tape is employed to place the WS 2 powder onto the tip of a fiber ferrule. Several runs of mechanical extraction are performed to reduce the thickness of WS 2 powder on the fiber tip. The fabricated WS 2 saturable absorber exhibits a saturation intensity of 548.6 MW/cm 2 , modulation depth of 4.1% and non-saturable loss of 67.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…24 Therefore, the saturable absorption (SA) properties of these novel 2D materials are an important research topic, as the mainstream saturable absorbers used for Q-switching and mode locking, e.g., doped crystals and SESAMs, still have some limitations such as narrow operation wavebands, limited response times, high cost, and complex fabrication processes. 34,35 A previous study confirmed that WS 2 exhibits strong SA properties and an ultrahigh optical damage threshold with a broad operational wavelength range from the visible range [36][37][38] up to the mid infrared range; 39,40 therefore, Q-switching 32,34,[36][37][38][40][41][42][43][44][45] and mode locking 32,35,39,[46][47][48] laser pulses can be generated by utilizing WS 2 as a saturable absorber in various laser systems. The fabrication of WS 2 film is relatively simple and low cost compared with that of the mainstream saturable absorbers used in commercial pulsed laser products.…”
Section: Introductionmentioning
confidence: 98%
“…24 Therefore, the saturable absorption (SA) properties of these novel 2D materials are an important research topic, as the mainstream saturable absorbers used for Q-switching and mode locking, e.g., doped crystals and SESAMs, still have some limitations such as narrow operation wavebands, limited response times, high cost, and complex fabrication processes. 34,35 A previous study confirmed that WS 2 exhibits strong SA properties and an ultrahigh optical damage threshold with a broad operational wavelength range from the visible range [36][37][38] up to the mid infrared range; 39,40 therefore, Q-switching 32,34,[36][37][38][40][41][42][43][44][45] and mode locking 32,35,39,[46][47][48] laser pulses can be generated by utilizing WS 2 as a saturable absorber in various laser systems. The fabrication of WS 2 film is relatively simple and low cost compared with that of the mainstream saturable absorbers used in commercial pulsed laser products.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, the types of material used for deposition has expanded enormously with the introduction of carbon nanotubes [9], graphene [10], topological insulators [11], transition metal chalcogenides [12][13][14], black phosphorus [15] and lately phosphorene [16]. The SA structures demonstrated in prior works include fiber ferrule [17], microfiber [18], and D-shaped fiber [19]. Despite the good Q-switching performance of the aforementioned SAs, the fabrication process of such an SA itself is rather difficult with ambiguous steps.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Wu et al demonstrated a Q-switched EDFL using WS 2 nanosheets, which were prepared using a liquid-phase exfoliation method and embedded in a polyvinyl alcohol (PVA) film [10]. Through a mechanical exfoliation technique, the WS 2 also can work as SA for Qswitching generation [11]. However, the signal-to-noise ratio of the formatted pulse is only up to 43dB.…”
mentioning
confidence: 99%